2019
DOI: 10.1111/1541-4337.12481
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria as Antifungal and Anti‐Mycotoxigenic Agents: A Comprehensive Review

Abstract: Fungal contamination of food and animal feed, especially by mycotoxigenic fungi, is not only a global food quality concern for food manufacturers, but it also poses serious health concerns because of the production of a variety of mycotoxins, some of which present considerable food safety challenges. In today's mega‐scale food and feed productions, which involve a number of processing steps and the use of a variety of ingredients, fungal contamination is regarded as unavoidable, even good manufacturing practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(143 citation statements)
references
References 288 publications
(307 reference statements)
2
139
0
2
Order By: Relevance
“…Overall, the results obtained are collected in Table 1 and allow for a number of considerations. The biotransformation experiments lasted four days and were performed in a 5 L fermenter in anaerobic conditions at 37 • C and using a starting fatty acid concentration of 3 g/L (stirring 170 rpm, pH 6.2); yields were calculated on the basis of the weight of isolated hydroxyacids; 2 According to preliminary experiments performed in an anaerobic flask, the hydroxy-acid derivatives were obtained in low yields (<5% by GC-MS analysis); 3 According to preliminary experiments performed in an anaerobic flask, the hydroxy-acid derivatives were not detected or their relative amounts were very low (<1% by GC-MS analysis); 4 The ee of compound 9 was not measured. Its NMR analysis indicates the presence of a single diastereoisomeric form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the results obtained are collected in Table 1 and allow for a number of considerations. The biotransformation experiments lasted four days and were performed in a 5 L fermenter in anaerobic conditions at 37 • C and using a starting fatty acid concentration of 3 g/L (stirring 170 rpm, pH 6.2); yields were calculated on the basis of the weight of isolated hydroxyacids; 2 According to preliminary experiments performed in an anaerobic flask, the hydroxy-acid derivatives were obtained in low yields (<5% by GC-MS analysis); 3 According to preliminary experiments performed in an anaerobic flask, the hydroxy-acid derivatives were not detected or their relative amounts were very low (<1% by GC-MS analysis); 4 The ee of compound 9 was not measured. Its NMR analysis indicates the presence of a single diastereoisomeric form.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of the probiotics market has fostered the biochemical studies of these species, especially those regarding the microorganism-human being interaction. Despite this fact, their use as biocatalysts for industrial biotransformation is restricted to a limited number of applications [3][4][5][6][7][8][9][10][11][12]. Among the most known probiotic bacteria, those belonging to the genus Lactobacillus and Bifidobacterium turned out to be the most promising for industrial purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their versatile metabolism and their ability to synthesize a wide range of beneficial metabolites in addition to LA, LAB are extensively used in biotechnology, food, and therapeutic products. Some of the applications of LAB include their use as additional hurdles for spoilage and pathogenic microorganisms, antifungal and anti-mycotoxigenic agents, bacteriocin producers, nutraceutical producers, probiotics and starter cultures, among others [6,10,[16][17][18][19]. After safety assessment, the United States (US) Food and Drug Administration (FDA) and the European Food Safety Agency (EFSA) included numerous LAB species and food additives derived from them on the generally recognized as safe (GRAS) inventory or accordingly granted the qualified presumption of safety (QPS) status [6,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, authors have shown that the antifungal activity of these compounds alone was too low to fully explain the antifungal activity observed [29,30]. Thus, other metabolites have been studied as the source of antifungal activity such as proteinaceous compounds, fatty acids, phenolic acid, hydrogen peroxide, and bacteriocins [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%